Lithofacial and paleogeographic analysis of the Burdigallian-Langhian formations of the Ukrainian Carpathian Foredeep - Cheremisska O.M.; Cheremissky Yu.V. (Днепропетровский национальный университет им. Олеся Гончара, 2019)
This paper addresses issues related to the complexity of the geological structure of the Burdigallian-Langhian sediments of the Stebnyk suite, which were formed in the Carpathian segment of Paratethys. The correlation of stratigraphic sections, based on a detailed description of the most complete sediments of the indigenous outcrops of the Stebnyk suite in the Sambir Unit of the Pre-Carpathian Foredeep, has been carried out. It was established that the sediments belong to a single tectono-sedimentation cyclic, the formation of which began with the deposition of red-coloured sediments and ended with the deposition of salt-bearing formations, which indicates the final closure of the Paratethys. A series of lithological columns was constructed taking into account the disjunctive and plicating faults, which allowed us to derive the true thickness of the Stebnyk suite deposits and determine its lithofacial structure. The results obtained became the basis for the construction of a lithological scheme for the distribution of lithofacies and a paleooceanographic sedimentation model of the research area. The aim of this work is to create a reconstruction of the environment of sedimentation in the Burdigallian-Langhian Age in the Sambir Unit of the Inner part of the Pre-Carpathian Foredeep. To obtain the results, the actual material obtained during the field observations was analyzed with the help of a complex of lithology-facial, geodynamical and petrographic methods. Due to the absence of the reliable paleontological data on deposits of the Miocene Stebnyk suite of the PreCarpathian basin, an attempt was made to partition the Stebnyk sedimentary sequence on lithological and formation features, based on the author's research and with incorporation of new materials of paleooceanography of the Carpathian segment of the Paratethys. On the basis of paleooceanographic data, connected with formation of sedimentary strata of Stebnyk suite (Carpathian basin), the latter can be attributed to the red-coloured formation of foothill plains and deltas. Taking into account the data of the researchers and their own observations, one can come to the conclusion that the age of the sediments, mapped on existing geological maps as Vorotyshcha suite in considerable areas of Sambir Unit (near the villages of Krasne, Pidlyvche, Lysovychi) is questionable. This conception required the stratification of deposits formed on the stage of sedimentogenesis in the Miocene within the studied segment of the Central Paratethys. For the first time for depositions of this age, the scheme of the palaeoceanographic situation and a lithological-facial model of the sedimentation environment with the reduction of the true thickness of sediments was constructed. The Burdigallian-Langhian deposits were formed under conditions of lacustrine-alluvial plains of arid climate, symbolizing the final closure of the Central Paratethys. The presence of a detailed model for the formation of Burdigallian-Langhian deposits allows us to identify a number of criteria for the search for minerals.
Keywords: lithology; літологія; міоцен; передкарпатський прогин; стебницька світа; геогенерація; паратетіс; miocene; pre-carpathian foredeep; stebnyk suite; geogeneration; paratethys; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен